Effects of radiation response modifiers given after lethal whole-abdominal irradiation. (4th March 2018) - Huang, Eng-Yen; Peng, Chen-Tzu; Wang, Chung-Chih
Abstract: Purpose: Although radiation is used to treat cancer and generate electricity, radiotherapy-induced complications and nuclear disasters are issues of great concern. The small bowel and bone marrow are the two major organs injured by radiation, especially that from nuclear disasters. The development of effective drugs to alleviate radiation injuries is very important. We tested potential radiation response modifiers given after irradiation to alleviate radiation injuries and mortality. Materials and methods: Xenografts of C33A tumor cells with or without galectin-1 expression were implanted in SCID mice. Local tumor irradiation (6 Gy) was used to study radiosensitivity. The rate and time of tumor growth to 2 cm were observed using the Kaplan-Meier method. C57BL/6N mice were used to study the effects of whole-abdominal or whole-body irradiation. Drug administration was as follows: (1) vehicle; (2) interleukin 6 (IL-6) (50 ng/day); (3) anginex (10 mg/kg/day) (galectin-1 antagonist); or (4) flagellin (0.2 mg/kg) (Toll-like receptor 5 agonist). These treatments were compared for tumor size and survival time. Results: The median time of tumor growth delay after 6 Gy irradiation was one week in tumors without galectin-1 expression, regardless of anginex administration. Anginex did not prolong the survival time after 18 Gy whole-abdominal irradiation. Flagellin did not prolong survival time after 18 Gy whole-abdominal irradiation. IL-6 prolonged the survival time after 18 Gy whole-abdominal irradiation, with 5% survival. This was the best result in treating lethal 18 Gy whole-abdominal irradiation. Other than IL-6, no drugs decreased the survival rate after 7.5 Gy whole-body irradiation. Conclusions: Anginex has no protective effects against radiation injury and no radiosensitized effects on tumors. IL-6 is a potential agent for treating radiation-induced lethal injuries to the small bowel. However, it is not suitable for treating bone marrow damage after whole-body irradiation.